THE NARRATIVE STRUCTURE IN SHORT STORY “IBLIS YANTASHIRU” BY TAUFIQ AL-HAKIM: A.J. GREIMAS PERSPECTIVE - Noriska, Zacky Aqsha; Zulkhairi; Jafar, Abzari; Syarifuddin; Kamila, Nisaul (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to analyze the narrative structure of Taufiq al-Hakim’s short story “Iblis Yantashiru” by identifying both its surface and deep structures through the lens of Algirdas Julien Greimas’s narrative semiotics. The analysis of the story’s narrative structure is crucial, as it significantly influences the comprehension of the overall meaning of the text. This research employs a descriptive qualitative approach, utilizing written data derived directly from the literary work. Data collection techniques include close reading, note-taking, and library research. The data were analyzed through several stages: identification, interpretation, analysis, and conclusion drawing. The structural analysis was conducted based on Greimas’s narrative semiotic framework, which encompasses the actantial structure, functional structure, main actant, surface structure and deep structure. The findings reveal that the short story’s structure is divided into four segments: the first segment presents the theme of “Nasik’s victory,” the second highlights “Nasik’s sincerity,” the third explores “the pact between Iblis and Nasik,” and the fourth emphasizes “self-interest.” Furthermore, the study identifies the main actant based on the actants found in these four segments: the principal sender is Nasik’s faith, while the main receiver as well as the subject is Nasik himself, who pursues the object of “upholding the truth.” In this pursuit, he is obstructed by the opposant, namely “Iblis,” and supported by the helpers, namely faith and an axe. Through the above structure, it can be concluded that the narrative of Taufiq al-Hakim’s short story “Iblis Yantashiru” contains unique narrative elements and a structural pattern consistent with A.J. Greimas’s narrative semiotics.